Table S5, Abundance of crenarchaeol, bacteriohopanetetrol I (BHT-I), bacteriohopanetetrol II (BHT-II), as well as C5 and C6 heterocyst glycolipids (HGs) in ODP cores at sites 964 and 967 - Elling, Felix J; Hemingway, Jordon D; Kharbush, Jenan; Becker, Kevin W; Polik, Catherine Ann; Pearson, Ann (In: Elling, FJ et al. (2021): Mediterranean sapropel bulk organic matter and biomarker concentrations and carbon isotope compositions [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.937082, 2021)
Carbon-normalized abundance of individual bacteriohopanetetrol (BHP) and heterocyst glycolipid (HG) compounds, as well as the relative abundance of BHT-I vs. BHT-II and HG-C5 compounds vs. HG-C6 compounds in ODP cores at sites 964 and 967. Concentration data for BHPs and HGs were generated using ultra high-performance liquid chromatography coupled to triple quadrupole mass spectrometry following Kusch et al. (2018) and Wörmer et al. (2012), respectively. This work was supported by the Gordon and Betty Moore Foundation.
Keywords: anoxia; Bacteriohopanepolyols; Biomarkers; d13C; d15N; GDGTs; heterocyst glycolipids; Mediterranean Sea; nitrogen cycle; organic matter; sapropels